Association Between Alkaline Phosphatase and Clinical Outcomes in Patients With Spontaneous Intracerebral Hemorrhage - Li, Sijia; Wang, Wenjuan; Zhang, Qian; Wang, Yu; Wang, Anxin; Zhao, Xingquan (Frontiers in Neurology, 2021)
Background: Spontaneous intracerebral hemorrhage (ICH) is associated with high rates of mortality and morbidity. Alkaline phosphatase (ALP) is related to increased risk of cardiovascular events and is also closely associated with adverse outcomes after ischemic or hemorrhagic stroke. However, there are limited data about the effect of ALP on clinical outcomes after ICH. Therefore, we aimed to investigate the relationship between serum ALP level and prognosis in ICH patients. Methods: From January 2014 to September 2016, 939 patients with spontaneous ICH were enrolled in our study from 13 hospitals in Beijing. Patients were categorized into four groups based on the ALP quartiles (Q1, Q2, Q3, Q4). The main outcomes were 30-day, 90-day, and 1-year poor functional outcomes (modified Rankin Scale score of 3–6). Multivariable logistic regression and interaction analyses were performed to evaluate the relationships between ALP and clinical outcomes after ICH. Results: In the logistic regression analysis, compared with the third quartile of ALP, the adjusted odds ratios of the Q1, Q2, and Q4 for 30-day poor functional outcome were 1.31 (0.80–2.15), 1.16 (0.71–1.89), and 2.16 (1.32–3.55). In terms of 90-day and 1-year poor functional outcomes, the risks were significantly higher in the highest quartile of ALP compared with the third quartile after adjusting the confounding factors [90-day: highest quartile OR = 1.86 (1.12–3.10); 1-year: highest quartile OR = 2.26 (1.34–3.80)]. Moreover, there was no significant interaction between ALP and variables like age or sex. Conclusions: High ALP level (>94.8 U/L) was independently associated with 30-day, 90-day, and 1-year poor functional outcomes in ICH patients. Serum ALP might serve as a predictor for poor functional outcomes after ICH onset.